2000
DOI: 10.1093/nar/28.10.2135
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA damage and a hypoxic response are induced by CoCl2 in rat neuronal PC12 cells

Abstract: Generation of reactive oxygen species (ROS) and activation of a transcriptional program that mimics the hypoxic response have been documented in cultured cells in the presence of cobalt chloride. We found that in the presence of hypoxia-mimicking concentrations of CoCl(2), mitochondrial but not nuclear DNA damage is induced in rat neuronal, PC12 cells. To our knowledge, this is the first documentation of induction of mitochondrial DNA (mtDNA) damage under these conditions. Likewise, we provide the first eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 51 publications
7
110
0
1
Order By: Relevance
“…Hypoxia-induced Cell Lysis Measurements-The method to induce chemical hypoxia was adapted from Wang et al (37). A stock solution of cobalt chloride was made in sterile double distilled water and various concentrations (25 M to 2 mM) were used for a 2-h treatment to induce hypoxia in Jurkat cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia-induced Cell Lysis Measurements-The method to induce chemical hypoxia was adapted from Wang et al (37). A stock solution of cobalt chloride was made in sterile double distilled water and various concentrations (25 M to 2 mM) were used for a 2-h treatment to induce hypoxia in Jurkat cells.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia was induced using cobalt chloride (37). Geldanamycin and radicicol both caused a significant increase of hypoxia-induced cell lysis in Jurkat cells.…”
Section: Geldanamycin-induced Lysis Acceleration In Bacterial Andmentioning
confidence: 99%
“…CoCl 2 has been widely used as a hypoxia-mimicking agent in mammalian systems (104)(105)(106)(107)(108), but the mechanisms by which it induces hypoxia-mimicking responses are not fully understood. However, Sre1p is required for adaptation to CoCl 2 in C. neoformans.…”
Section: Fungi With Srebp Orthologsmentioning
confidence: 99%
“…It has been reported that chemical hypoxia=reoxy-genation was simulated by the addition and the removal of chemicals such as NaN 3 or CoCl 2 or Na 2 S 2 O 4 (Rose et al, 1998;Wang et al, 2000;Zhang et al, 2005). The neurons are extremely sensitive to hypoxia and reoxygenation insult (Faroqui et al, 1994).…”
Section: Cell Toxicity Induced By Na 2 S 2 Omentioning
confidence: 99%